Currency portfolio of external debt, exchange rate cyclicality, and consumption volatility - Fujii, Eiji (CESifo, Center for Economic Studies & Ifo Institute, 2020)
Even though external debt can play a buffer role against adverse shocks to assist consumption smoothing, it may also exert a volatility amplifying effect, depending on the currency of denomination and the cyclicality of the borrower’s exchange rate. We empirically investigate the nexus between the debt denomination portfolio, exchange rate cyclicality, and consumption volatility of low- and middle-income countries. On constructing the debt-weighted effective exchange rates, we examine how the denomination portfolio affects the debtors' exchange rate cyclicality to influence the consumption response to transitory income shocks. We find that portfolio concentration enhances exchange rate pro-cyclicality, which makes consumption more volatile when income shocks occur. Our results suggest that portfolio diversification is a useful tool for countries with original sin to hedge against bumpy consumption paths.
10419/219105
Keywords: Graue Literatur; external debt; currency portfolio; original sin; exchange rate cyclicality; consumption volatility